Digital Library Management at IAIN Kendari - Safrudin, Moh; Evariyanti, Runi; Badarwan (IAIN KENDARI, 2026)
The purpose of this research is to find out the digital library management at IAIN Kendari digital library. The method in this research uses a qualitative method with a descriptive approach. Data collection techniques were carried out by observation, interviews, and documentation then analyzed by data reduction, data presentation, and conclusions. The subjects of this research consisted of the head of the library, IT and Multimedia staff, management staff, and students. The results of this study indicate that digital library management at IAIN Kendari includes planning carried out from the determination of the vision and mission then analyzing the needs, followed by the design of various digital platforms, the funds used are funds derived from DIPA IAIN budgeted every year. The organization of the digital library at IAIN Kendari is structured and planned, but when it still lacks human resources, especially in the field of IT experts. The implementation of the digital library at IAIN Kendari uses an automated system in managing book collections, facilities owned by the digital library include opac, repository, proquest, e-books, wifi, computer rooms, and digital absences, but the e-book collection is still very limited at 499 book titles, and there are still obstacles in accessing wifi. Supervision of the digital library at IAIN Kendari is carried out by each staff on duty in the room and evaluations are carried out on every Monday to conduct regular monitoring. The implications of this research suggest that IAIN Kendari needs to prioritize the recruitment of qualified IT personnel and expand its digital e-book collection to improve the quality of digital library services. Institutionally, this research provides a foundation for library management policy development based on the POAC management functions in the context of Islamic higher education institutions with limited resources